A single-atom nano-enzyme, a mulch containing the same and a preparation method thereof
Patent Information
- Application Number
- CN202611236794.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-09
AI Technical Summary
然而,其只证明了聚乳酸材料在水中的降解率,无法外推至土壤环境中的实际降解行为
本发明提供的单原子纳米酶的制备方法普适性好,通用性强,整套工艺适用于铁、钴、镍、铜、锌、锰六种金属单原子纳米酶的制备;采用该方法制备的单原子纳米酶具有良好的稳定性,能够耐受500℃以上的高温,作为助剂加入地膜中,与地膜共同挤出加工,加工后完全保留催化活性。
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomimetic nanoenzyme technology, and particularly relates to a single-atom nanoenzyme, a mulch film containing the nanoenzyme, and a preparation method thereof. Background Technology
[0002] Mulching technology is a core yield-increasing measure in modern agriculture, with significant effects in warming, moisture retention, and weed control, occupying an important position in agricultural production in my country and globally. However, traditional polyethylene (PE) mulch film is extremely difficult to degrade in soil, and its long-term use has led to increasingly severe "white pollution" in farmland, causing serious damage to soil structure and ecological risks. Therefore, the development of biodegradable mulch film materials has become an urgent need in the agricultural sector.
[0003] Currently, biodegradable polymer materials such as polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), and poly-3-hydroxybutyrate (P3HB) have become the mainstream alternatives to traditional PE mulch films. Their degradation process relies on the spontaneous hydrolysis of polymer chains in the soil environment and the enzymatic action of microbial enzymes. However, relying solely on natural degradation, the degradation efficiency of these materials in actual farmland environments is extremely limited, making it difficult to meet the actual needs of agricultural production for controlled degradation of mulch films. Therefore, it is urgent to introduce degradation-promoting strategies. Existing degradation-promoting schemes mainly include two categories: one is the direct addition of natural proteases or lipases, and the other is the incorporation of oxide nanoparticles as nanoenzyme catalytic aids.
[0004] CN115491126A discloses a biodegradable liquid mulch film prepared from enzymatically hydrolyzed lignite, comprising the following raw materials in parts by weight: 85-90 parts deionized water, 5-10 parts enzymatically hydrolyzed lignite, 5-8 parts guar gum emulsion, 3-5 parts polylactic acid, 2.5-3.5 parts glycerol, and 1-2.5 parts polyvinyl alcohol. This patent promotes the degradation of polylactic acid by adding enzymatically hydrolyzed lignite to the mulch film; however, the preparation of enzymatically hydrolyzed lignite requires 7 days, a relatively long cycle, and specific post-processing steps, increasing production costs.
[0005] CN117447849A discloses a fully biodegradable mulch film for garlic and its preparation method. The garlic-specific fully biodegradable mulch film comprises PLA-PBAT copolymer, microcrystalline cellulose, starch, biodegradation aids, and polyhydroxyalkanoates; the biodegradation aids include cellulase and amylase. This patent achieves targeted degradation of different components in the mulch film by adding biodegradation aids. However, the melt extrusion temperature of the mulch film is controlled at around 180℃, at which temperature the activity of the biodegradation aids cannot be guaranteed, resulting in very limited improvement in degradation promotion effect.
[0006] CN117924894A discloses a controllable degradable polylactic acid (PLA) material and its preparation method, comprising, by mass percentage: 0.1-5% anti-hydrolysis agent, 0.1-20% nano-hydrolytic enzyme, and 75-100% PLA. The nano-hydrolytic enzyme includes at least one of Ce-MOFs, Zr-MOFs, Cu-MOFs, ZIF, and their derivatives. This patent significantly improves the degradation efficiency of PLA in water by dispersing and embedding nano-enzymes with a metal framework structure into the PLA material, forming complexes with the oxygen atoms of the PLA ester groups, activating the ester groups, and catalyzing their hydrolysis. It also exhibits good tolerance and stability. However, it only demonstrates the degradation rate of PLA in water and cannot extrapolate to the actual degradation behavior in soil environments.
[0007] Therefore, developing a single-atom nanoenzyme degradation aid and applying it to a biodegradable mulch film system to significantly improve the degradation rate of the mulch film is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0008] To address the shortcomings of existing technologies, the present invention aims to provide a single-atom nanozyme, a mulch film containing the nanozyme, and a preparation method thereof. The present invention uses ZIF-8 derived nitrogen-doped porous carbon as a carrier, adds metal salts, and purifies it by impregnation, calcination, and acid washing to obtain a single-atom nanozyme with an M-N4 (M represents metal) configuration. This nanozyme is incorporated into biodegradable mulch film as an adjuvant, which can accelerate the degradation of biodegradable mulch film and has a high degradation rate.
[0009] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing single-atom nanozymes, the method comprising the following steps: (1) Zinc nitrate hexahydrate reacts with 2-methylimidazole to give ZIF-8; (2) The ZIF-8 is immersed in a solution of metal salt to obtain a metal precursor; (3) The metal precursor is calcined and acid-washed to obtain the single-atom nanozyme.
[0010] This invention uses ZIF-8-derived nitrogen-doped porous carbon as a carrier, which is impregnated with metal salt, calcined, acid-washed, and purified to anchor a single metal atom at the N atom site, forming a single-atom nanozyme with an M-N4 configuration. This single-atom nanozyme has enzyme-like activity, which can not only catalyze the hydrolysis of ester groups and destroy the polymer structure of the mulch film, but also activate oxygen or water molecules in the soil to convert them into reactive oxygen species, which attack the weak sites in the polymer chain of the mulch film, thus significantly improving the degradation rate of the mulch film.
[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The purpose and beneficial effects of the present invention can be better achieved and realized through the following preferred technical solutions.
[0012] Preferably, the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:(3.5-4.5), for example, 1:3.5, 1:3.7, 1:3.9, 1:4.1, 1:4.3, 1:4.5, etc.
[0013] Preferably, in step (1), the reaction is carried out in a solvent.
[0014] Preferably, the solvent includes methanol and / or ethanol.
[0015] Preferably, the reaction is carried out at room temperature.
[0016] Preferably, the reaction time is 3-5 hours, such as 3 hours, 4 hours, 5 hours, etc.
[0017] Preferably, the reaction is followed by centrifugation, washing, or drying.
[0018] Preferably, in step (2), ZIF-8 is pretreated before impregnation.
[0019] Preferably, the pretreatment step includes treating ZIF-8 in a vacuum at 75-85°C (e.g., 75°C, 77°C, 79°C, 81°C, 83°C, 85°C, etc.) for 3-5 hours (e.g., 3 hours, 4 hours, 5 hours, etc.).
[0020] Preferably, the metal salt includes metal nitrates and / or metal chlorides.
[0021] Preferably, the metal nitrate includes any one of ferric nitrate, cobalt nitrate, nickel nitrate, copper nitrate, zinc nitrate, or manganese nitrate.
[0022] Preferably, the metal chloride salt includes any one of ferric chloride, cobalt chloride, nickel chloride, copper chloride, zinc chloride, or manganese chloride.
[0023] Preferably, in step (2), the solvent of the solution includes methanol and / or ethanol.
[0024] Preferably, in step (2), the immersion temperature is 0-30℃, such as 0℃, 2℃, 4℃, 6℃, 8℃, 10℃, 12℃, 14℃, 16℃, 18℃, 20℃, 22℃, 24℃, 26℃, 28℃, 30℃, etc.
[0025] Preferably, the soaking time is 6-9 hours, such as 6 hours, 7 hours, 8 hours, 9 hours, etc.
[0026] Preferably, in step (3), the calcination is carried out in a nitrogen atmosphere.
[0027] Preferably, the flow rate of the nitrogen gas is 50-70 mL / min, such as 50 mL / min, 55 mL / min, 60 mL / min, 65 mL / min, 70 mL / min, etc.
[0028] Preferably, the calcination includes a first stage and a second stage.
[0029] In this invention, segmented calcination helps maintain the integrity of the material's skeleton structure, inhibits the collapse of the material skeleton, and thus ensures that it has a high specific surface area (BET). The higher BET gives the material a stronger ability to adsorb air and moisture, thereby providing favorable conditions for regulating the micro-ecological environment necessary for the degradation of the mulch film.
[0030] Preferably, the temperature of the first stage is 500-530℃, such as 500℃, 505℃, 510℃, 515℃, 520℃, 525℃, 530℃, etc.
[0031] Preferably, the heating rate in the first stage is 1.5-2.5℃ / min, such as 1.5℃ / min, 2℃ / min, 2.5℃ / min, etc.
[0032] Preferably, the heat preservation time in the first stage is 2.5-3.5 hours, such as 2.5 hours, 3 hours, 3.5 hours, etc.
[0033] Preferably, the temperature of the second stage is 900-950℃, such as 900℃, 910℃, 920℃, 930℃, 940℃, 950℃, etc.
[0034] Preferably, the heating rate in the second stage is 2.5-3.5℃ / min, such as 2.5℃ / min, 3℃ / min, 3.5℃ / min, etc.
[0035] Preferably, the heat preservation time in the second stage is 4.5-5.5 hours, such as 4.5 hours, 5 hours, 5.5 hours, etc.
[0036] Preferably, the pickling is performed using sulfuric acid.
[0037] Preferably, the pickling process further includes water washing or drying.
[0038] Preferably, the single-atom nanozyme includes any one of iron single-atom nanozyme, cobalt single-atom nanozyme, nickel single-atom nanozyme, copper single-atom nanozyme, zinc single-atom nanozyme, or manganese single-atom nanozyme.
[0039] Preferably, the preparation method of the single-atom nanozyme specifically includes the following steps: (1) Zinc nitrate hexahydrate and 2-methylimidazolium were dissolved in a solvent at a molar ratio of 1:(3.5-4.5), reacted at room temperature for 3-5 h, centrifuged, washed, and dried to obtain ZIF-8; (2) The ZIF-8 is treated in a vacuum at 75-85℃ for 3-5 hours and then immersed in a solution of metal salt at 0-30℃ for 6-9 hours to obtain a metal precursor; (3) The metal precursor is placed in a nitrogen atmosphere and heated to 500-530℃ at a heating rate of 1.5-2.5℃ / min, and held for 2.5-3.5h. Then, it is heated to 900-950℃ at a heating rate of 2.5-3.5℃ / min and held for 4.5-5.5h. The precursor is then washed with sulfuric acid, washed with water, and dried to obtain the single-atom nanozyme.
[0040] In a second aspect, the present invention provides a single-atom nanozyme, which is prepared by the preparation method described in the first aspect.
[0041] Thirdly, the present invention provides a mulch film comprising a substrate and the single-atom nanoenzyme described in the second aspect.
[0042] Preferably, the substrate comprises any one or a combination of at least two of polylactic acid, polybutylene terephthalate, or poly-3-hydroxybutyrate.
[0043] Preferably, the amount of the single-atom nanozyme is 0.1-0.5% based on the mass of the substrate, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc.
[0044] This invention controls the addition of single-atom nanozymes within the range of 0.1-0.5%, effectively maintaining the mechanical properties of the mulch film while ensuring its excellent degradation performance. Insufficient addition reduces the degradation efficiency of the mulch film, while excessive addition leads to soil compaction and secondary pollution.
[0045] Compared with the prior art, the present invention has the following beneficial effects: The method for preparing single-atom nanozymes provided by this invention has good universality and versatility. The entire process is applicable to the preparation of single-atom nanozymes of six metals: iron, cobalt, nickel, copper, zinc, and manganese. The single-atom nanozymes prepared by this method have good stability and can withstand high temperatures above 500°C. When added to mulch film as an adjuvant and co-extruded with the mulch film, the catalytic activity is completely retained after processing.
[0046] Even with a low addition amount of single-atom nanozymes (0.1-0.5%), mulch films can still maintain excellent catalytic activity and degradation effect without damaging the mechanical properties of the film. The degradation rate of farmland mulch films is 75-93% after 3 months. Among them, mulch films containing zinc single-atom nanozymes achieve a degradation rate of over 90% after 3 months. Alternatively, single-atom nanozymes with suitable degradation cycles can be selected according to the soil environment and crop growth needs.
[0047] The single-atom nanozymes provided by this invention involve six metals: iron, cobalt, nickel, copper, zinc, and manganese. These are all trace elements needed for soil or plant growth. Adding a small amount of single-atom nanozymes to the mulch film results in no heavy metal residue after degradation and will not pollute the soil. Detailed Implementation
[0048] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.
[0049] The source information of some raw materials in this embodiment of the invention is as follows: PLA: Nature Works 5032D (USA); PBAT: BASF, Germany, C1200 granules.
[0050] Example 1 This embodiment provides an iron single-atom nanozyme and its preparation method, the preparation method comprising the following steps: (1) 29.7g zinc nitrate hexahydrate and 32.8g 2-methylimidazole were dissolved in 100mL methanol and reacted at room temperature for 4h. After centrifugation, the mixture was washed with methanol and dried under vacuum at 60℃ to obtain ZIF-8. (2) The ZIF-8 was treated in a vacuum at 80°C for 4 hours, then immersed in a methanol solution of 0.15 mol / L ferric nitrate and kept at 15°C for 8 hours to obtain the metal precursor; (3) The metal precursor was placed in a tube furnace with a nitrogen flow rate of 60 mL / min and heated to 520°C at a heating rate of 2°C / min. The temperature was held for 3 h, and then heated to 900°C at a heating rate of 3°C / min. The temperature was held for 5 h, washed with 0.5 mol / L dilute sulfuric acid, washed with water until neutral, and dried to obtain iron single-atom nanozyme.
[0051] Example 2 This embodiment provides a cobalt single-atom nanozyme and its preparation method, the preparation method comprising the following steps: (1) 29.7g zinc nitrate hexahydrate and 28.7g 2-methylimidazole were dissolved in 100mL ethanol and reacted at room temperature for 3h. After centrifugation, the mixture was washed with ethanol and dried under vacuum at 60℃ to obtain ZIF-8. (2) The ZIF-8 was treated in a vacuum at 75°C for 5 hours, then immersed in a methanol solution of 0.15 mol / L cobalt nitrate and kept at 0°C for 9 hours to obtain the metal precursor; (3) The metal precursor was placed in a tube furnace with a nitrogen flow rate of 50 mL / min and heated to 500°C at a heating rate of 1.5°C / min. The temperature was held for 3.5 h, and then heated to 950°C at a heating rate of 2.5°C / min. The temperature was held for 5.5 h, washed with 0.5 mol / L dilute sulfuric acid, washed with water until neutral, and dried to obtain cobalt single-atom nanozyme.
[0052] Example 3 This embodiment provides a nickel single-atom nanozyme and its preparation method, the preparation method comprising the following steps: (1) 29.7g zinc nitrate hexahydrate and 36.9g 2-methylimidazole were dissolved in 100mL ethanol and reacted at room temperature for 5h. After centrifugation, the mixture was washed with ethanol and dried under vacuum at 60℃ to obtain ZIF-8. (2) The ZIF-8 was treated in a vacuum at 85°C for 3 hours, then immersed in an ethanol solution of 0.15 mol / L nickel nitrate and kept at 30°C for 7 hours to obtain a metal precursor; (3) The metal precursor was placed in a tube furnace with a nitrogen flow rate of 70 mL / min and heated to 530°C at a heating rate of 2.5°C / min. The temperature was held for 2.5 h, and then heated to 920°C at a heating rate of 3.5°C / min. The temperature was held for 4.5 h. The precursor was washed with 0.5 mol / L dilute sulfuric acid, washed with water until neutral, and dried to obtain nickel single-atom nanozyme.
[0053] Example 4 The only difference from Example 1 is that ferric nitrate is replaced with copper nitrate of equal concentration, while the amounts of other components and the preparation methods are the same as in Example 1.
[0054] Example 5 The only difference from Example 1 is that ferric nitrate is replaced with zinc nitrate of equal concentration, while the amounts of other components and the preparation methods are the same as in Example 1.
[0055] Example 6 The only difference from Example 1 is that ferric nitrate is replaced with manganese chloride of the same concentration, while the amounts of other components and the preparation methods are the same as in Example 1.
[0056] Example 7 The only difference from Example 1 is that the calcination has only one stage, with the temperature increased to 900°C at a rate of 3°C / min, and calcined at 900°C for 5 hours. The amount of other components and the preparation method are the same as in Example 1.
[0057] Comparative Example 1 The only difference from Example 1 is that steps (1)-(2) are replaced by: dissolving 29.7g zinc nitrate hexahydrate and 24.15g ferric nitrate in 50mL methanol to obtain solution A, dissolving 32.8g 2-methylimidazole in 50mL methanol to obtain solution B, stirring at room temperature and centrifuging to collect the precipitate, and then washing the precipitate with ethanol by centrifugation and vacuum drying to obtain the metal precursor. The amounts of the remaining components and the preparation methods are the same as in Example 1.
[0058] Application Example 1 This application example provides a mulch film comprising 40 parts PLA, 60 parts PBAT, and 0.3 parts of the iron single-atom nanozyme from Example 1, which are mixed, granulated, and blow-molded at 150°C to form a mulch film with a thickness of 22 μm.
[0059] Application Example 2 The only difference from Application Example 1 is that the iron single-atom nanozyme is replaced with 0.1 parts of the cobalt single-atom nanozyme of Example 2, while the amounts of the remaining components and the preparation methods are the same as in Application Example 1.
[0060] Application Example 3 The only difference from Application Example 1 is that the iron single-atom nanozyme is replaced with 0.5 parts of the nickel single-atom nanozyme of Example 3, while the amounts of the remaining components and the preparation methods are the same as in Application Example 1.
[0061] Application Example 4-7 and Comparative Application Example 1 The only difference from Application Example 1 is that the iron single-atom nanozyme is replaced with an equal amount of the single-atom nanozyme in Examples 4-7 and Comparative Example 1, while the amounts of other components and the preparation methods are the same as in Application Example 1.
[0062] Comparative Application Example 2 The only difference from Application Example 1 is that the amount of iron single-atom nanozyme added is 0.05 parts, while the amount of other components and the preparation method are the same as in Application Example 1.
[0063] Comparative Application Example 3 The only difference from Application Example 1 is that the amount of iron single-atom nanozyme added is 1 part, while the amount of other components and the preparation method are the same as in Application Example 1.
[0064] Comparative Application Example 4 The only difference from Application Example 1 is that no single-atom nanozyme is added, while the amounts of the remaining components and the preparation methods are the same as in Application Example 1.
[0065] Performance testing Degradation rate: Tested according to GB / T 19277.1-2011, the specific test steps are as follows: (1) Pre-experiment preparation: Take well-rotted compost (passed through a 1.0cm sieve) and place it in a constant temperature incubator at 58±2℃. Aerate and activate it for culture. If the CO2 produced by the inoculum relative to each gram of volatile solids in the container is 50-150mg within 10 days, the activity of thermophilic microorganisms is confirmed to meet the standard. Cut the plastic film sample into 2cm×2cm pieces and use an elemental analyzer to determine the total organic carbon (TOC) content. Each sample was tested in 3 parallel tests, and the average value was used as the baseline data for calculating the degradation rate. Weigh the inoculum and the mulch film sample separately, mix them thoroughly, and then dispense them into the corresponding reaction vessels. Start the DKR-DA24 unit and perform a 24-channel air tightness self-test, calibrate the CO2 sensor, and calibrate the electronic flow meter. Fill the blank group, positive control group and test sample group according to the ratio, and record the reactor number and total weight of materials for each group; Seal the reactor, connect the inlet and outlet gas detection pipelines, enter the sample information into the computer software, and automatically collect CO2 data every 2 hours. Set the temperature to a constant 58℃, introduce humidified air, run continuously for 24 hours, collect baseline CO2 data, and confirm that the system has no leaks and the baseline is stable. (2) Routine operation and maintenance during the trial period (90 days, fixed daily operation) Daily monitoring records: The computer exports the cumulative CO2 data for the day and records the real-time temperature of each channel simultaneously; Water replenishment procedure: Weigh the total weight of the reactor daily. When the water loss is greater than 3%, add preheated deionized water to maintain the water content. Venting: Open the container for 5 minutes daily to ventilate and loosen the compost substrate, preventing anaerobic fermentation; Anomaly investigation: If there are sudden changes in CO2 concentration in a single channel, temperature deviation, or gas line blockage, promptly detect leaks and clear any obstructions in the pipeline; Weekly visual observation: Record the compost color, odor, and sample fragment disintegration status, and archive photos; (3) Trial termination and data processing (day 90) Stop ventilation, cool to room temperature, and remove all compost residue; Residue sieving: Undegraded sample residue was separated using a 2mm sieve, washed, dried, weighed, and the disintegration rate was calculated; Data Summary: Export the cumulative CO2 curve for the entire cycle. The software automatically subtracts the blank baseline and calculates the degradation rate daily. The degradation rate calculation formula is as follows: ; Wherein, Dt: biodegradation rate on day t, % MCO2,T: Cumulative CO2 mass in the sample channel, mg; MCO2,B: Average CO2 mass of the blank control group (arithmetic mean of all blank reactors), mg; ThCO2: Theoretical maximum CO2 yield at complete mineralization of the sample, mg; Determination of experimental validity: If the degradation rate of the positive control group is ≥70% after 45 days, the data of this experiment are valid; otherwise, the experiment should be repeated.
[0066] The performance of the mulch film provided in the corresponding test cases and comparative application examples according to the above performance testing methods is shown in Table 1. Table 1 As shown in Table 1, when the single-atom nanozymes provided by this invention are added to the mulch film, the degradation rate of the mulch film is over 75% after 3 months. Among them, the zinc single-atom nanozymes have the best degradation effect on the mulch film, with a degradation rate as high as 90.5% after 3 months.
[0067] In Application Example 7, the single-atom nanozymes used were not calcined in stages. This reduced the porosity in the single-atom nanozyme structure, inhibiting its absorption of air and moisture, which led to a significant decrease in the degradation rate of the mulch film.
[0068] In contrast, Application Example 1 did not use the preparation method of the present invention to prepare single-atom nanozymes, which resulted in an increase in the concentration of metal atoms in ZIF-8 and a decrease in the degradation rate of the mulch film.
[0069] In contrast to application example 2, the amount of single-atom nanozymes added was relatively small, resulting in a decrease in the degradation rate of the mulch film; in contrast to application example 3, the amount of single-atom nanozymes added was too large, and the residual metals would pollute the soil.
[0070] Compared with Comparative Application Example 4, the degradation rate of the mulch film with added single-atom nanozymes in Application Examples 1-7 of the present invention is significantly improved.
[0071] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A method for preparing a single-atom nanozyme, characterized in that, The preparation method includes the following steps: (1) Zinc nitrate hexahydrate reacts with 2-methylimidazole to give ZIF-8; (2) The ZIF-8 is immersed in a solution of metal salt to obtain a metal precursor; (3) The metal precursor is calcined and acid-washed to obtain the single-atom nanozyme.
2. The preparation method according to claim 1, characterized in that, The molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:(3.5-4.5); Preferably, in step (1), the reaction is carried out in a solvent; Preferably, the solvent includes methanol and / or ethanol; Preferably, the reaction is carried out at room temperature; Preferably, the reaction time is 3-5 hours; Preferably, the reaction is followed by centrifugation, washing, or drying.
3. The preparation method according to claim 1 or 2, characterized in that, In step (2), the ZIF-8 is further pretreated before impregnation; Preferably, the pretreatment step includes: treating ZIF-8 in a vacuum at 75-85°C for 3-5 hours; Preferably, the metal salt includes metal nitrates and / or metal chlorides; Preferably, the metal nitrate includes any one of ferric nitrate, cobalt nitrate, nickel nitrate, copper nitrate, zinc nitrate, or manganese nitrate; Preferably, the metal chloride salt includes any one of ferric chloride, cobalt chloride, nickel chloride, copper chloride, zinc chloride, or manganese chloride; Preferably, in step (2), the solvent of the solution includes methanol and / or ethanol.
4. The preparation method according to any one of claims 1-3, characterized in that, In step (2), the immersion temperature is 0-30℃; Preferably, the soaking time is 6-9 hours.
5. The preparation method according to any one of claims 1-4, characterized in that, In step (3), the calcination is carried out in a nitrogen atmosphere; Preferably, the flow rate of the nitrogen gas is 50-70 mL / min; Preferably, the calcination includes a first stage and a second stage; Preferably, the temperature of the first stage is 500-530℃; Preferably, the heating rate in the first stage is 1.5-2.5℃ / min; Preferably, the heat preservation time in the first stage is 2.5-3.5 hours; Preferably, the temperature of the second stage is 900-950℃; Preferably, the heating rate in the second stage is 2.5-3.5℃ / min; Preferably, the heat preservation time in the second stage is 4.5-5.5 hours.
6. The preparation method according to any one of claims 1-5, characterized in that, The pickling process uses sulfuric acid. Preferably, the pickling process further includes water washing or drying; Preferably, the single-atom nanozyme includes any one of iron single-atom nanozyme, cobalt single-atom nanozyme, nickel single-atom nanozyme, copper single-atom nanozyme, zinc single-atom nanozyme, or manganese single-atom nanozyme.
7. The preparation method according to any one of claims 1-6, characterized in that, The preparation method specifically includes the following steps: (1) Zinc nitrate hexahydrate and 2-methylimidazolium were dissolved in a solvent at a molar ratio of 1:(3.5-4.5), reacted at room temperature for 3-5 h, centrifuged, washed, and dried to obtain ZIF-8; (2) The ZIF-8 is treated in a vacuum at 75-85℃ for 3-5 hours and then immersed in a solution of metal salt at 0-30℃ for 6-9 hours to obtain a metal precursor; (3) The metal precursor is placed in a nitrogen atmosphere and heated to 500-530℃ at a heating rate of 1.5-2.5℃ / min, and held for 2.5-3.5h. Then, it is heated to 900-950℃ at a heating rate of 2.5-3.5℃ / min and held for 4.5-5.5h. The precursor is then washed with sulfuric acid, washed with water, and dried to obtain the single-atom nanozyme.
8. A single-atom nanozyme, characterized in that, The single-atom nanozyme is prepared by the preparation method according to any one of claims 1-7.
9. A type of mulch film, characterized in that, The mulch film includes a substrate and the single-atom nanozyme as described in claim 8.
10. The mulch film according to claim 9, characterized in that, The substrate includes any one or a combination of at least two of polylactic acid, polybutylene terephthalate, or poly-3-hydroxybutyrate. Preferably, the amount of the single-atom nanozyme is 0.1-0.5% based on the mass of the substrate (100%).
Citation Information
Patent Citations
Special full-biodegradable mulching film for garlic and preparation method thereof
CN117447849A
Controllable degradation polylactic acid material and preparation method thereof
CN117924894A